Caracterização da resistência a anti-helmínticos e análise molecular de populações de Haemonchus contortus frente aos benzimidazóis no município de Mossoró RN - Bezerra, Ana Carla Diógenes Suassuna (Universidade Federal Rural do Semi-Árido, 2014)
The increase in anthelmintic resistance in gastrointestinal nematodes on small ruminants became a worldwide issue on the development of livestock. In order to assess the resistance scenario in that context in the Rio Grande do Norte region, in vivo and in vitro resistance tests were carried out in 30 rural properties using chemicals in the avermectin, salicylanides, benzimidazoles and imidatiazols groups. For the in vivo test, group I was used as control and four other experimental groups received oral medication, being group II given albendazole (10 mg/kg), group III levamisole (7.5 mg/kg), group IV closantel (5.0 mg/kg) and group V ivermectin (0.2 mg/kg). The nematode infection was determined using fecal egg count (FEC) essays and the efficiency of each treatment was analyzed by the fecal egg count reduction test (FECRT). For the in vivo e in vitro tests, using tiabendazole, the necessary concentration to inhibit 50% of egg hatching (EC50) and assays with a 50% inhibition of larval development (LD50) were assessed, however 50% of larval development and migration inhibition assays (LD50) essays were carried out using ivermectin. For the molecular analysis Haemonchus contortus/property were isolated for the calculation of the frequency of resistant and sensitive alleles for single nucleotide polymorphisms (SNPs): F220Y, F167Y and E198A. The results obtained from in vivo tests showed that resistance was detected for all of the drugs, with leavamisole and closantel appearing as the most effective treatments with FECRT results of 84.3% and 74.6%, respectively. In the in vitro assays, tiabendazole had a result in the hatching test of EC50 0.598 µg/ml (95% IC: 0.323-0.818), while exhibiting in the larval development test a LD50 and LD99 0.518 µg/ml(95% IC: 0.432-0,887) and 4.359 µg/ml (95% IC: 3.047-8.178), respectively. For ivermectin in the larval development test, DL50 0.637 µg/ml(95% IC: 0.382 0.903 µg/ml) e DL99 19.56 µg/ml(95% IC: 11.44 46.55 µg/ml) was observed, while in the migration essay the LD50 value was 16.337 µM (95% IC: 12.7-21.3 µM). In the molecular analysis a higher frequency of the resistant allele for SNP F200Y was observed, presenting higher percentage values of 85.81% and 73.11%, while the F167Y resistant alleles had lower values ranging from 2.93% to 43.73%. In the E198A SNP, only sensitive alleles were detected. Assessing the scenario of anthelmintic resistance in the region, one notices that it s established for the main existing drugs on the market
Anthelmintic resistance characterization and molecular analysis of Haemonchus contortus populations upon benzimidazoles in the city of Mossoró RN
Keywords: Keywords: Small ruminants, gastrointestinal parasites, polymorphism; Pequenos ruminantes, parasitos gastrintestinais, polimorfismo; CIENCIAS AGRARIAS::MEDICINA VETERINARIA